Revitalisasi Kesehatan Masyarakat: Dampak IBS Fitness Center di Sragen Melalui Keterlibatan Olahraga - Septianingrum, Kartika; Munandar, Hamzani Ari; Irfan, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to investigate the impact and contribution of the IBS Fitness Center to the revitalization of the Sragen community through exercise. The existence of fitness centres such as IBS Fitness Center promises the potential to improve the lifestyle and overall health of the community. Data was collected through interviews and direct observation with managers, fitness centre members, and the surrounding community. The results showed that the existence of the IBS Fitness Center has had a positive impact on the sports health awareness of the people of Sragen. The programs have raised awareness of the importance of a healthy lifestyle and empowered the local economy through job creation and promotion of local products. The study also identified several challenges, such as participation rates that still need to be improved and financial accessibility for some communities. Therefore, the study recommends increasing outreach and education efforts, as well as strengthening cooperation with the government and private sector to support future fitness programs. This research not only provides a deeper understanding of community revitalization through sports in Sragen but also provides useful guidance for policymakers and health practitioners to improve the health and well-being of society at large. Keywords: IBS Fitness Center, Revitalization, Sport health